2012
DOI: 10.1037/a0029564
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of psychodynamic psychotherapy outcomes: Evaluating the effects of research-specific procedures.

Abstract: The aim of this research was to examine the extent to which the use of research-specific procedures in psychodynamic psychotherapy impacts upon treatment effectiveness and which variables moderate this potential relationship. Effects of audio/video recording of sessions, use of treatment manuals, and checks of treatment fidelity were examined. A meta-analysis was conducted on randomized controlled trials of psychodynamic psychotherapy. Forty-six independent treatment samples totaling 1615 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 110 publications
5
40
0
1
Order By: Relevance
“…In the field of psychodynamic treatment of adults this situation began to change in recent years, with the publication of a number of important reviews and meta-analyzes (De Matt, Jonghe, Schoevers & Dekker, 2009;Gerber et al, 2011;Leichsenring, 2005;Leichsenring & Rabung, 2008;Leichsenring, Rabung, & Leibing, 2004;Shedler, 2012;Town, Diener, Abbass, Leichsenring, Driesse, & Rabung, 2012). Based on Randomized Controlled Trials (RCT) or not, these revisions showed that psychodynamic psychotherapy is at least equal to other forms of treatment regarded as evidence-based and that patients receiving this treatment not only keep the gains after its end, but often continue to improve.…”
mentioning
confidence: 99%
“…In the field of psychodynamic treatment of adults this situation began to change in recent years, with the publication of a number of important reviews and meta-analyzes (De Matt, Jonghe, Schoevers & Dekker, 2009;Gerber et al, 2011;Leichsenring, 2005;Leichsenring & Rabung, 2008;Leichsenring, Rabung, & Leibing, 2004;Shedler, 2012;Town, Diener, Abbass, Leichsenring, Driesse, & Rabung, 2012). Based on Randomized Controlled Trials (RCT) or not, these revisions showed that psychodynamic psychotherapy is at least equal to other forms of treatment regarded as evidence-based and that patients receiving this treatment not only keep the gains after its end, but often continue to improve.…”
mentioning
confidence: 99%
“…ENDURING EFFECTS OF PSYCHODYNAMIC TREATMENTS 6 (Abbass, Town, & Driessen, 2011;Driessen, Cuijpers, de Maat, Abbass, de Jonghe & Dekker, 2010;Town, Abbass, & Hardy, 2011) and some have claimed that the benefits of psychodynamic treatments increase over time (e.g., Leichsenring, Rabung & Leibing, 2004;Town et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Such intrapsychic changes may account for long-term treatment benefits [of psychodynamic treatments]. (pp 102, 105) Seeking to produce evidence of the sustained benefits of psychodynamic treatments beyond treatment completion, an increasing number of meta-analyses have indicated that the benefits of psychodynamic treatments at post-treatment are maintained at follow-up, and in some instances increase over time (Abbass, Hancock, Henderson, & Kisely, 2006;Abbass, Kisely, & Kroenke, 2009;Leichsenring, Rabung & Leibing, 2004;Town et al, 2012). For example, Abbass and colleagues (Abbass, Hancock, Henderson, & Kisely, 2006;Abbass, Kisely, & Kroenke, 2009) conducted a series of meta-analyses of controlled trials of short-term dynamic therapy (STDT) and found that STDT was superior to various types of no-treatment or minimal treatment controls on a variety of outcome measures and that the effects were sustained or grew over time.…”
mentioning
confidence: 98%
“…The introduction of treatment manuals allowed interventions under empirical investigation to be operationalised to best support therapy delivery in line with designed treatment structures [8,9]. Manualisation enabled an intervention to be monitored for Treatment Fidelity levels according to the research protocols [4,7].…”
Section: Fidelity Toolsmentioning
confidence: 99%
“…Adherence is expressed as the delivery of a key component or technique of the treatment [9]. In contrast, competence measures assess the skills or accuracy with which the treatment is implemented [22,23].…”
Section: Fidelity Toolsmentioning
confidence: 99%